2022
DOI: 10.3390/ijms232112814
|View full text |Cite
|
Sign up to set email alerts
|

PITHIA: Protein Interaction Site Prediction Using Multiple Sequence Alignments and Attention

Abstract: Cellular functions are governed by proteins, and, while some proteins work independently,most work by interacting with other proteins. As a result it is crucially important to know theinteraction sites that facilitate the interactions between the proteins. Since the experimental methodsare costly and time consuming, it is essential to develop effective computational methods. We presentPITHIA, a sequence-based deep learning model for protein interaction site prediction that exploits thecombination of multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The trend in the field is that the current models the field is publishing involve attention. PITHIA demonstrated that the use of the transformer architecture with attention yielded the best results when testing different architectures of the model [67]. Therefore, for the foreseeable future, in order for models to compete with the current state-of-the-art, they will need to incorporate an attention mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The trend in the field is that the current models the field is publishing involve attention. PITHIA demonstrated that the use of the transformer architecture with attention yielded the best results when testing different architectures of the model [67]. Therefore, for the foreseeable future, in order for models to compete with the current state-of-the-art, they will need to incorporate an attention mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, when testing the impact of additional features such as a PSSM, physiochemical characteristics, or evolutionary conservation, the use of MSAs alone yielded the best results [67]. PITHIA demonstrates the power of MSAs within the attention mechanism compared against other architectures and features.…”
Section: 21mentioning
confidence: 97%
See 3 more Smart Citations